Rancang Bangun Aplikasi Pendaftaran Santriwati Baru Dengan Fitur Computer Based Test(CBT) Menggunakan Algoritma Fisher Yates Berbasis Web : (Studi Kasus : Ma’had Tarbiyatul Banaat Ummu Sulaim Balikpapan) - Muhammad Nurfalah Setiawan; Eko Edy Susanto (Jurnal Penelitian Rumpun Ilmu Teknik, 2022)
Ma'had Tarbiyatul Banaat Ummu Sulaim Balikpapan is a non-formal education institution and a Quran memorization (tahfidz) center based on a specialized Muslim women's Islamic boarding school. The registration process for new female students is currently done manually using spreadsheets and written exams. To address this issue, a solution is proposed in the form of an online registration application with a Computer-Based Test (CBT) feature that randomizes questions using the Fisher Yates algorithm. The research methodology used in this study includes data collection needs analysis, application design, and application testing. The results of the research indicate that this application allows prospective female students to fill out their personal information and take CBT exams online, with questions randomized using the Fisher Yates algorithm. Additionally, the administration of new female student registrations can efficiently manage student data and exam questions. This research has been successfully designed with the hope of assisting prospective female students in the registration process and simplifying administrative tasks for the staff. The use of the Fisher Yates algorithm for randomizing CBT questions also yields good results in minimizing cheating during the examination process.